Economic Sources of Gain in Stock Repurchases - Chan, Konan; Ikenberry, David; Lee, Inmoo (Journal of Financial and Quantitative Analysis, 2004)
Abstract Previous studies offer a mixed understanding of the economic role of stock repurchases. This paper investigates three key economic motivations—mispricing, disgorging free cash flow, and increasing leverage—by evaluating cross-sectional differences in both the initial market reaction and long-run performance. The initial reaction provides some support for the mispricing story. However, subsequent earnings-related information shocks suggest that the initial market reaction is incomplete and that long-run performance may be informative. The long-horizon return evidence is most consistent with the mispricing hypothesis and, to some degree, the free cash flow hypothesis. We find little support for the leverage hypothesis.